(Implementation of the Electre (Elimination Et Choix Traduisan La Realite) Method in a Healthy Food Menu Decision Support System for Toddlers in the Sasak Area Health Center Pasisie Using the Php And Databse Mysql Programming Language) - Mardison; Syafrika Deni Rizki; Larissa Navia Rani; Agung Ramadhanu; Repelita Witri (Universitas Putra Indonesia YPTK Padang, 2020)
Healthy food menu for toddlers is selected based on criteria that have been determined by Puskesmas Sasak Ranah Pasisie. The selection of healthy food menus for toddlers is carried out by the institution as the selection of healthy foods for toddlers. The selection of toddler food menus still uses traditional methods that have not been systemized. With these problems, a decision support system is applied using the La Raelite Elimination Et Choix method. This method is able to give subjective and inuitive considerations of the criteria factors that are considered important influences on alternative choices. Decision Support System is a computer technology solution that can be used to support decision making that is complex in problem solving in an organization, in order to be able to determine the selection of the best competitive and superior healthy food menu from the many toddler food menus then the process of selecting a healthy toddler food menu that determines the optimal alternative is fast and efficient.